Stressor and Coping Mechanism of Divorced Woman - Wahyuni, Sri; Pranata, Satriya; Yosafianti Pohan, Vivi (Scripta Medica, 2024)
Background/Aim: Widowhood is the status given to women who have separated from their husbands, either by death or divorce. The high divorce rate in Indonesia has an impact on the number of divorced women. In Indonesia, women with divorced status are still stigmatized, where the stigma and perception of divorced women in the community are still skewed. The phenomenon of divorced women or also known as widows is not only a form and pattern of life in Indonesia but also occurs throughout the world because it is one of the processes of individual life in society in the world. The formation of a negative stigma from the community makes women who experience divorce will face many problems that can increase stress and make women psychologically disturbed. To overcome the conflict experienced, individuals have a coping mechanism as a way to defend themselves against changes that occur both within themselves and from outside themselves. The purpose of this study was to explore the sources of stress and coping mechanisms for stress of divorced women in Cirebon Regency, West Java, Indonesia Methods: This research is a qualitative research with a phenomenological approach. The research participants amounted to 8 women with a divorce status of less than 2 months who experienced mild and moderate stress in dealing with the new status of divorce in Cirebon Regency. The selection of research participants used a convenience sampling technique. Data collection methods using in-depth interview techniques and administering questionnaires perceived stress scale (PSS) to determine a person’s level of psychological stress . Data analysis in this study used the Colaizzi method. This study identified two themes, namely the sources of stress of divorced women and coping mechanisms for stress built by divorced women. Results: This research identified two themes, namely sources of stress for divorced women and coping mechanisms for stress that develop in divorced women. Sources of stress include social status, negative stigma from society, the process of raising children without a husband, economic factors, fear of facing life in the future, relationships with ex-husbands and their families. These various stresses do not prevent divorced women from continuing their life process. This is because of the coping mechanisms made by divorced women so that the stress they experience does not have a negative impact on their lives. These coping mechanisms include self-management, enjoying the process, diverting problems, telling other people about problems, strengthening spirituality and self-reflection. Conclusion: From the Thematic Results, participants obtained two major themes, namely: Sources of stress of divorced women (social status, negative stigma of society, the process of parenting without the assistance of the husband, economic factors, low self-esteem, fear of facing future life, relationship with ex-husband and his family) and coping mechanisms of divorced women (self-management, enjoying the process, diversion of problems, telling problems to others, strengthening spirituality and self-reflection